Comparativo de carga Polínica y Rendimiento de miel de abeja con tres tipos de alza Melaria en colmenares del bajo Mayo, San Martín - Lozano Ríos, Jhin (2012)
This research paper entitled "Comparison of pollen load and performance of honey up with three types of low apiaries Melaria Bajo Mayo, San Martín", aimed to: determine the yield of honey per hive through three types of honey supers in harvest months of April-May 2012 in the Lower zone apiaries Mayo (Zapatero and Banda Districts of Shilcayo) Determine pollen production per hive in harvest months of April- May 2012 and evaluate the characteristics physical - chemical honey obtained in work zones. The development of the research was carried out in the districts of Zapatero and Shilcayo Band - San Martin province, we compared the results of both district, using randomized complete design (DCA) with 4 treatments and 3 replications conforming 12 units experimental. The treatments were: T1 = Performance Full honey increases (compared Witness), T2 = yield of honey in three quarters of the rise and T3 = average honey yield increases. The most significant findings were: The highest yield of honey per hive per type of hike in T1 (yield increases HONEY complete) obtained the highest average was in the town of Las Palmas with 22.2 kg of honey and in the town of Zapatero was 17.0 kg. groups respectively and T1 (yield of honey in complete hikes) reached the highest average Brix with 79%, followed by T3 treatments (yield of honey in stockings hikes) and T2 (yield of honey in three quarters of the rise) who obtained averages of 78.6% and 78% respectively Brix. This same behavior was observed at pH reached, with the T1 (yield increases of honey in full) which obtained a pH of 6.0, followed by T3 treatments (yield of honey in stockings hikes) and T2 (yield of honey in three quarter rise) who obtained mean pH of 5.0 and 4.0 respectively. Keywords: honey, pollen load, Colmenares, honey yield